Admissible vector fields and related diffusions on infinite-dimensional manifolds - Elworthy, K. D.; Zhi, Ming Ma (Ukrains’kyi Matematychnyi Zhurnal, 1997)
A variation on the notion of “admissibility” for vector fields on certain infinite-dimensional manifolds with measures on them is described. It leads to the construction of associated diffusions and Markov semigroups on these manifolds via Dirichlet forms. Some classes of concrete examples are given.